Correlation between Anxiety and Depression with Quality of Life among Chronic Obstructive Pulmonary Disease Patients - Dessy Mizarti; Deddy Herman; Yessy S Sabri; Amel Yanis (Jurnal Respirologi Indonesia, 2019)
Background: Anxiety and depression among COPD patients can lead to physical limitation, lung function deterioration, risk of exacerbation and poor quality of life. This study aims to investigate correlation between anxiety and depression with quality of life among COPD patients Method: This was cross sectional analytic study recruiting COPD patients in Pulmonary outpatient setting in Dr. M. Djamil Central Hospital Padang and Achmad Mochtar Hospital Bukittinggi from January to March 2017. Samples were recruited through consecutive technique (accidental sampling). Result: Results showed from 101 COPD patients, average age was 65,54 + 9,99 years old. Mostly were male 83,17%, basic education 71,29%, low economical status 58,42%, married 81,19%, ex smoker 71,29%, severe Brinkman index 60,40%. There was correlation between gender (p value =0,002) and marital status (p value =0,010) with anxiety and or depression. Severe COPD patients tend to suffer from anxiety, depression, anxiety and depression, as many as 34,78%, 100% and 54,55%, respectively. Most COPD patients who suffered from anxiety and depression had poor quality of life 28,57%. There was correlation between anxiety and or depression with quality of life among COPD patients p-value= 0,005. COPD patients in D group often had poor quality of life 82,14%. There was correlation between COPD population group and quality of life (p-value=0,001). Conclusion: Anxiety and depression could occur in every stage of COPD, especially severe COPD. There was correlation between anxiety and or depression with quality of life so thus COPD treatment should embrace the comorbid factors. (J Respir Indo 2019; 39(2): 121-9)